Breaking Barriers: The Fight Against Discrimination Among Indonesian Muslim Minority in America - Nadiatus Salama (Indonesian Journal of Islamic Literature and Muslim Society, 2024)
Discrimination against minority groups based on race, religion, and other characteristics has a long-standing history in the United States. This study explores how Indonesian Muslims in major urban areas across the US confront and resist discrimination. Through phenomenological analysis, data were gathered from 16 Indonesian participants residing in eight different states. The findings reveal that Indonesian Muslims employ strategies such as staying calm, exercising self-control, seeking clarification, speaking up, and reporting incidents to authorities to combat discrimination. These coping mechanisms reflect the complexity of discrimination faced by this minority group and underscore the need for robust legal frameworks and collaborative efforts to promote tolerance and respect for diversity. The study offers valuable insights for activists, religious leaders, legal advocates, and academics working to foster an inclusive society. It also emphasizes the necessity for further research, particularly with larger and more diverse samples, to understand the long-term impacts and to develop targeted interventions that support Indonesian Muslims and other minority groups in the US.